Assessing the Prospects of Accelerated Graduation of the Least Developed Countries - Patrick Guillaumont; Alassane Drabo (Fondation pour les études et recherches sur le développement international (FERDI), 2013)
This paper provides a first systematic examination of the graduation trends and prospects after the 4th UN Conference on the least developed countries and the adoption of the Istanbul Plan of Action (IPoA). A major statement of the IPoA is "the aim of enabling half the number of least developed countries to meet the criteria for graduation by 2020". This goal has been referred to or reiterated in several official UN documents (UN Resolutions of December 2012). While considered at the time of the Istanbul Conference as moderately realistic, it has evidenced a change in international attitudes towards graduation.Revised version January 2014
Keywords: O19; 330; graduation